Quit-smoking counselling in Dutch midwifery practices: Barriers to the implementation of national guidelines. (April 2019) - Hopman, Petra; Springvloet, Linda; de Josselin de Jong, Sanne; van Laar, Margriet
Highlights: Many midwives regard the provision of quit-smoking counselling as their task. Most midwives start quit-smoking counselling, but few go through all counselling steps. Many midwifes refer smoking clients to the GP for quit-smoking counselling. Half of the midwives would like to discuss smoking cessation more often and/or easily. A perceived lack of client motivation is the major obstacle in quit-smoking counselling. Abstract: Objective: Although smoking during pregnancy can have severe health consequences for the (unborn) child, 9% of Dutch pregnant women smoke at any time during their pregnancy. Midwives in the Netherlands are a responsible party in the provision of quit-smoking counselling for pregnant women by means of the 7-step `V-MIS' intervention, but in practice the implementation appears to be suboptimal. The purpose of the present study was to assess the provision of quit-smoking counselling by midwives, and to clarify the nature and extent of any existing barriers and needs in the provision of quit-smoking counselling in Dutch midwifery settings. Methods: An online questionnaire to the target population of Dutch midwives ( N ≈ 3150) was set out in the spring of 2016. The questionnaire included items on the provision of quit-smoking counselling for pregnant women, and on possible barriers and needs regarding the provision of this counselling. Descriptive statistics were used to analyse weighed data from 135 midwives representative for the Dutch setting in terms of age, function, and region. Results: Eighty-one percent of the midwives inquire about smoking profile (V-MIS step 1) but only 10% go through all the V-MIS counselling steps (i.e. up to discussing postnatal passive smoking and smoke free breastfeeding, step 7). Although 74% of the midwives regard it as their task to provide quit-smoking guidance to pregnant women, 77% perceive referral to a professional as a useful strategy (mostly to the GP; 74%). For 61% of the midwives, their clients' lack of motivation undermines the provision of quit-smoking counselling. Other hindering factors are the perceived lack of free brochures (54%), simple tools or gadgets (51%), and financial consequences for the midwife (37%) and/or the client (22%). Conclusion: The smoking cessation intervention strategy currently imposed in Dutch midwifery practices (V-MIS) is being used by midwives, however its implementation may considerably benefit from strengthening skills in motivational interviewing techniques, provision of supporting materials, and structural embedding of GP referral. Based on the study's findings, practical recommendations are made to facilitate the provision of quit-smoking counselling in (international) midwifery settings.